DESAIN DAN RANCANG BANGUN DRONE PENABUR BENIH PERTANIAN - Saputro, Harjono; Riyanto, Handoko; Adesta, Erry Yulian Triblas; Muhida, Riza; Mulyana; Riza, Muhammad; Tanjung, Tia (Badan Penerbit Universitas Muria Kudus, 2026)
Modern technological progress has inspired numerous innovations that enhance efficiency in human activities, with agriculture remaining one of the most vital sectors for sustaining national economies. Appropriate technologies increase productivity while reducing dependence on traditional practices that demand excessive time and labor. This research presents the design and development of an agricultural drone created for seed spreading. The system employs a 300 Rpm DC motor that drives a propeller to ensure even seed distribution. Performance evaluation compared manual seed spreading and the drone-based method. Results demonstrated that manual spreading required an average of 3.33 hours per kilogram of seeds, whereas the drone accomplished the same task within 1 minute 20 seconds (80 seconds) per kilogram. These findings confirm that drone-assisted seeding offers an efficient and practical approach that supports the advancement of modern agriculture.